1999
DOI: 10.1007/s002640050385
|View full text |Cite
|
Sign up to set email alerts
|

Uncemented total hip arthroplasty in the elderly

Abstract: Between January 1991 and December 1994, 132 uncemented total hip arthroplasties (THA) were performed on 125 patients over 65 years of age; of which 102 arthroplasties, performed in 90 patients, were followed for at least 4 years. One revision was necessary following fracture of an acetabular component secondary to trauma. The post-operative Harris hip score (HHS) ranged from 87 to 99. Radiologically there were no signs of subsidence of more than 3 mm, nor of osteolysis. Five patients experienced thigh pain. Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 13 publications
2
9
0
Order By: Relevance
“…Our study had 27% and 29% complication rate in the cemented and the non-cemented groups, respectively, which is similar to other reports that show similar complications between the two groups [22][23][24][25]. Other studies of elder patients undergoing THA have shown good to excellent clinical outcomes with predictable relief of pain and improvement in function.…”
Section: Discussionsupporting
confidence: 93%
“…Our study had 27% and 29% complication rate in the cemented and the non-cemented groups, respectively, which is similar to other reports that show similar complications between the two groups [22][23][24][25]. Other studies of elder patients undergoing THA have shown good to excellent clinical outcomes with predictable relief of pain and improvement in function.…”
Section: Discussionsupporting
confidence: 93%
“…10,11). There is, in fact, increasing evidence in the literature suggesting that cementless implants are not contra-indicated in patients of advanced age and can be considered as a safe technique [31,[36][37][38][39][40].…”
Section: Discussionmentioning
confidence: 98%
“…These 32 exclusions left 149 patients (160 THAs; two patients excluded had bilateral off-the-shelf implants). Sixty patients (65 THAs) were 70 years and older at the time of surgery with an average age of 75 years (range, 70-86 years) and average body mass index of 27 (range, [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. The minimum followup was 24 months (mean, 35 months; range, 24-60 months).…”
Section: Methodsmentioning
confidence: 99%